Use and problems in the language of discipline-based qualification statements: learning from Tuning and its analogues - Clifford Adelman (Universidad de Deusto, 2014)
This essay is an empirical account of English language use, across three continents, in 40 Tuning and analogous discipline-based statements of desired demonstrated competences and learning outcomes in higher education. It is primarily concerned with lexical and semantic matters, takes the perspective of the student as the primary reader and beneficiary of these statements, and is as much proscriptive as it is analytical. It provides frequencies of verbs used in such statements, flags commonly but unacceptable verbs and syntax, offers a different grouping of competence-oriented verbs from that inherited from Bloom et al's Taxonomy, and suggests what we should do in revisiting statements of learning outcomes that have taken root in the literature.